Housing demolition and financial market investment: evidence from Chinese household data. Issue 36 (2nd August 2022) - Shi, Xiuzhen; He, Zekai
ABSTRACT: This paper estimates the impact of housing demolitions on households' investment behaviour in financial markets in China using a large microeconomic data set. This study provides new evidence on the effect of demolitions on families' investment behaviour from a natural experiment created by housing demolition and compensation events. We find that housing demolitions significantly increase households' participation in risky financial markets. Households' portfolio choices in responses to demolitions vary substantially across household characteristics. The affected households in urban areas and those with cash compensation are more likely to participate in risky asset markets, while the affected low-income families decrease investment in financial markets. To understand the underlying mechanisms, we propose a framework of how housing demolitions increase households' financial asset allocation. Our results indicate that changes in precautionary motive for savings and risk preference hold substantial importance.